Purification of supercoiled HPV-16 E6/E7 plasmid using a modified monolithic support - Amorim, Lúcia Filipa Alves (2018)
Made available in DSpace on 2018-08-02T15:29:08Z (GMT). No. of bitstreams: 1 3478_6908.pdf: 3466230 bytes, checksum: 4193144dc8a7b98b4b84d73be2320664 (MD5) Previous issue date: 2014-07-17